Upaya Meningkatkan Keterampilan Menulis Teks Prosedur dengan Model Demonstrasi Siswa Kelas VII -C SMP Negeri 10 Muaro Jambi - Sulistiani Sulistiani (Jurnal Ilmiah Dikdaya, 2022)
Classroom Action Research (CAR) which aims to improve the quality of learning and learning achievement of class VII students of SMP Negeri 10 Muaro Jambi in the 2018/2019 academic year through a demonstration model. This research was carried out in two cycles. Data collection is done by using direct observation through practice and written tests. The action taken is to carry out demonstration model group work starting with a model through pieces of paper that will be arranged into a sequence of photo frame procedure texts then students stick them on cardboard. Followed by giving assignments in groups how to make pencil holders from used plastic bottles of drinks according to practice. Demonstration will be made into a procedure text. Based on the results of the study, it can be concluded that the application of the demonstration learning model is very effective, improving the quality of learning as seen from the behavior and attitudes of students in activities while at the same time improving learning outcomes. This is supported by research data which shows an increase in the percentage value of completeness carried out in the implementation of each cycle. The pre-cycle value was 69.79 after the research was carried out, in Cycle one the average value was 80.47, in the second cycle, it increased to 89.53.